Guidelines for caring stroke patient during the transition from hospital to home with family participation in the Northern Region - Pongtae, Kodchaporn; Hongsri, Parimon (Thai Journal of Nursing, 2025)
This research and development aimed to explore the problems and needs of care, and to develop guidelines for caring stroke patient during the transition from hospital to home with family participation. The study was carried out in three stages. Stage 1 involved exploring patient care problems and needs. Stage 2 was the development of patient care guidelines for caregivers. Stage 3 examined the effectiveness of patient care guideline implementation using a quasi-experimental study with one group pretest posttest design. The sample included 27 pairs of caregivers and patients. Data were analyzed using descriptive statistics and paired t-test. The results showed that caregivers lacked confidence and were not involved in care planning. Patients had readmissions and inconsistent follow-up, with insufficient resources. The developed patient care guidelines consisted of two parts: for professional nurses and for caregivers. It covered identifying issues and needs in care, preparing knowledge, and training skills in caregivers. The study of the effectiveness of the care guidelines showed that the overall readiness score of the caregivers was at a good level. The ability to perform daily activities of the patients was significantly better after using the care guidelines than before (p < .05) and the patients’ quality of life significantly improved to a good level (p < .05).